New Mexico and the Pimería Alta The Colonial Period in the American Southwest - Douglass, John (University Press of Colorado, 2017)
Colonialism and the process of state expansion into new territories far from the capitol and mother country have occurred for thousands of years across the globe. Within the American Southwest, colonial encounters and the processes of colonialism played out in notably divergent manners through time and space. The chapters in New Mexico and the Pimería Alta: The Colonial Period in the American Southwest, focus on the two major areas of the Southwest that witnessed the most intensive and sustained colonial encounters: the New Mexico Colony and the Pimería Alta. Although these broad areas share a similar early colonial history, the particular mix of players, socio-historical trajectories, and social relations within each area both led to, and were transformed by, markedly diverse colonial encounters. Understanding these different mixes of players, history, and social relations provides the foundation for conceptualizing the enormous changes wrought by colonialism throughout the region.